Effects Of Teaching Grammar of Writing in Primary School - Shaxnoza Razakova; Gulchehra Agzamkhanova (Euro Asian Journal Publishing, 2024)
Introducing advanced methods of teaching using modern pedagogic and information and communication technologies, to fundamentally improve the system of teaching foreign languages to the growing young generation, training specialists who can speak these languages freely, and on the basis of this, in order to create conditions and opportunities for their achievements of world civilization and wide use of world information resources, development of international cooperation and communication. The purpose of the article is to improve the writing skills of primary school English learners, teach them new writing techniques, and increase their interest in English.
Keywords: teaching; writing; primary school ages; spelling